2017
DOI: 10.1093/pubmed/fdx097
|View full text |Cite
|
Sign up to set email alerts
|

Trends in diabetes and pre-diabetes prevalence and diabetes awareness, treatment and control across socioeconomic gradients in rural southwest China

Abstract: The prevalence of pre-diabetes and diabetes and the level of diabetes awareness, treatment and control increased substantially across all socioeconomic gradients in rural southwest China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
4
16
0
Order By: Relevance
“…The present study revealed that older individuals with higher education levels had higher awareness and control rates of diabetes than those with lower education levels. This is consistent with the results of some studies [32][33][34]. Previous studies have con rmed that education level is positively correlated with the health literacy level in patients with diabetes [35].…”
Section: Discussionsupporting
confidence: 92%
“…The present study revealed that older individuals with higher education levels had higher awareness and control rates of diabetes than those with lower education levels. This is consistent with the results of some studies [32][33][34]. Previous studies have con rmed that education level is positively correlated with the health literacy level in patients with diabetes [35].…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, our findings are similar to those of a study in Chi Linh, a northern city in which 15.9% of those aged 50-69 years were living with diabetes [10], a study in the south central coast of Vietnam that reported prevalence rates of 8.1% for diabetes and 50.1% for prediabetes [9], and a study conducted in the South Central Coast province, namely Khanh Hoa that reported a 20% prevalence of diabetes among those aged over 40 years [21]. Our results also align with those of other Asian middle-aged populations, for example, Thailand ( > 13.5% with diabetes in 2014) or China ( > 11.3% with diabetes in 2016) [22], Japanese adults aged over 40 years (men: 19.4%; women: 9.1%) [23], and adults in the United States [24]. Nevertheless, the estimate was lower than that of a study conducted during 2006-2014 in Hong Kong, China, which found that roughly 40% of the age group 40-79 years had diabetes [25].…”
Section: Discussionsupporting
confidence: 86%
“…Risk factor control in high CVD risk individuals is seen as an essential method of CVD primary prevention. However, several studies have demonstrated that the control of CVD risk factors was insufficient [12][13][14][15]. The same may be said for our studies on high CVD risk individuals in Inner Mongolia [16].…”
Section: Introductionsupporting
confidence: 65%